Historical (1850–2014) Aerosol Evolution and Role on Climate Forcing Using the GISS ModelE2.1 Contribution to CMIP6. (1st August 2020) - Bauer, Susanne E.; Tsigaridis, Kostas; Faluvegi, Greg; Kelley, Maxwell; Lo, Ken K.; Miller, Ron L.; Nazarenko, Larissa; Schmidt, Gavin A.; Wu, Jingbo
Abstract: The Earth's climate is rapidly changing. Over the past centuries, aerosols, via their ability to absorb or scatter solar radiation and alter clouds, played an important role in counterbalancing some of the greenhouse gas (GHG) caused global warming. The multicentury anthropogenic aerosol cooling effect prevented present‐day climate from reaching even higher surface air temperatures and subsequent more dramatic climate impacts. Trends in aerosol concentrations and optical depth show that in many polluted regions such as Europe and the United States, aerosol precursor emissions decreased back to levels of the 1950s. More recent polluting countries such as China may have reached a turning point in recent years as well, while India still follows an upward trend. Here we study aerosol trends in the Coupled Model Intercomparison Project Phase 6 (CMIP6) simulations of the GISS ModelE2.1 climate model using a fully coupled atmosphere composition configuration, including interactive gas‐phase chemistry and either an aerosol microphysical (MATRIX) or a mass‐based (One‐Moment Aerosol, OMA) aerosol module. Results show that whether global aerosol radiative forcing is already declining depends on the aerosol scheme used. Using the aerosol microphysical scheme, where the aerosol system reacts more strongly to the trend in sulfur dioxide (SO2 ) emissions, global peak direct aerosol forcing was reached in the 1980s, whereas the mass‐based scheme simulates peak direct aerosol forcing around 2010. Plain Language Summary: The National Aeronautics and Space Administration (NASA) Earth system model, GISS ModelE2.1, has released new interactive composition climate simulations from 1850 to 2014 into the Coupled Model Intercomparison Project Phase 6 (CMIP6) Diagnosis, Evaluation, and Characterization of Klima protocol archive. The GISS model includes two different schemes to simulate aerosols in the atmosphere, driven by natural and anthropogenic emissions. The two aerosol schemes differ by degree of complexity. One model better resolves aerosol microphysical processes, while the other model has more detailed chemistry regarding secondary organic aerosol formation. The models simulate different trends in aerosol radiative forcing. An evaluation with satellite data between 2001 and 2014 demonstrates that the model with more detailed aerosol microphysics has reached maximal aerosol direct forcing in the 1980s and is since on a decreasing global forcing trajectory. This has implications for using the trends over recent decades as predictive for greenhouse‐gas related changes in the future. Key Points: A discussion is presented of the AMIP aerosol simulations for the years 1850 to 2014 of the GISS ModelE2.1 for CMIP6, using two different aerosol schemes The detailed treatment of aerosol microphysical processes greatly impacts aerosol forcing and forcing trends One model suggests that Earth has already exceeded the maximum negative forcing effects of anthropogenic aerosol in the 1980s